TICS IN THE YVU PORA RENDA INDIGENOUS COMMUNITY - Luis Troche Ojeda, Pablo; David Britez Prieto, Alejandro; Daniel Velázquez Silva, Jorge; Vanessa Ruiz Diaz de Salvioni, Viviana; Armoa, Alcides (Revista Gênero e Interdisciplinaridade, 2023)
The following investigative work allowed us to analyze the lack of influence of Information and Communication Technologies -ICT- in the Yvu Pòra Renda Indigenous Community, ICTs have already reached the most remote places through, for the most part, the smart phones. This reality must be read properly from school, to take advantage of these technologies for the benefit of learning with cultural and linguistic relevance. The methodology used is mixed research under the Quantitative and Qualitative approach, data collection was carried out through interviews and surveys. The results made it possible to identify shortcomings in the use of ICTs in the teaching-learning processes, difficulties in the indigenous community regarding the use of ICTs, and interaction problems, which could be overcome with the appropriate and oriented use of ICTs. ICT, this facilitated the generation of a series of recommendations regarding their use, with a view to improving the indigenous community and thus favoring the general academic results and the interculturality present in the community, actions that could be equally beneficial in other institutions or countries. Through the use of ICTs, the indigenous community can make good use of drones, GPS, software, digital mapping platforms, and data management. Several indigenous peoples in the region have found an ally in technology to strengthen their territories and their identity.